Thematic unit on Aztec, Incan and Mayan culture - Gratton, Carly Marie (Kansas State University, 2014)
The principal objective of this paper is to provide a thematic teaching unit that explores the Aztec, Incan and Mayan cultures of Latin America, designed for a level II Spanish course. It contains theoretical underpinnings for teaching language, culture and literature while incorporating concepts related to the development of communicative competence; processing instruction; the use of scaffolding in the zone of proximal development; target language instruction; and the inclusion of authentic materials and language in the classroom. The classroom management strategies explained and used throughout the unit include pre, during and post-reading activities; small group activities that help to develop communicative competence through negotiation of meaning and interactional feedback; focused tasks and collaborative output tasks; the use of structured input, structured output and information exchange; the PACE approach to grammar teaching; and the incorporation of authentic aural and written texts. Lesson plans for an eighteen day unit consisting of 40 minute classes are outlined; the lesson objective, necessary materials, time needed for each activity, and expected results of each lesson are included. Each lesson activity is made clear through a description of the activity and instructions for the teacher. The daily lesson plans contain authentic and teacher-created materials that can be found in the appendices section. At the end of the thematic unit, students complete cumulative activities that relate indigenous cultures to present-day life in Latin America through investigating the influence of Aztec words on the Spanish and English languages, analyzing a poem about Peru, and reading an article about discrimination against Mayan descendants in Central America, Mexico and the U.S.
Keywords: Maya; Aztec; Inca; Authentic materials; Unit; Communicative competence; Teaching literature; Education, General (0515); Language, Modern (0291); Teacher Education (0530)